Effect of melanin on diffuse reflectance spectroscopy of human skin tissue / Nabilah Ramli - Ramli, Nabilah (2013)
Diffuse reflectance spectroscopy in the visible and near infrared spectral ranges is an effective and extensively used technique for non-invasive study and characterization of various biological tissues. The effect of melanin on diffuse reflectance spectroscopy of human tissue was study in this research. To investigate this, diffuse reflectance spectra were collected from human skin at palm and back of hand of the sample since palm has thick epidermis and a few melanin pigments as compared to back of hand that consist many melanin pigment. Other than that, the temperature effect also consider in this investigation. The measurement was taken at room temperature and high temperature respectively with the small increment of temperature where the changes in temperature are sensed by the skin, which is well-designed to counteract these changes. Experimental result show that the general reduction in reflectance intensity observed from longer to shorter wavelengths is due to melanin absorption since melanin is the dominant chromophore responsible for the reflectance lineshape. As expected, back of hand has higher melanin absorption compared to palm, whereas the palm without melanin absorption. The diffuse reflectance spectrum exhibits a ‘W’ pattern between 530nm t0 600nm wavelengths, which is an indication of observation of hemoglobin. The effect of temperature gives a gradual decrease of the reflectance spectrum from low temperature to high temperature. This is cause by fluctuation of blood when heat is applied on skin, blood supply to the skin increases again as the arterioles dilates. Exposure to heat causes blood vessels to dilate, allowing heat to dissipate from the skins surface and resulting in a flushed or red appearance which effects the reflectance measurement.